2015
DOI: 10.1016/j.ijheatmasstransfer.2015.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Developing convective flow in a square channel partially filled with a high porosity metal foam and rotating in a parallel-mode

Abstract: The development of three-dimensional heat transfer and fluid flow in a square channel rotating in a parallel-mode has been investigated numerically. The duct is partially occupied by a foam material of high porosity ε≥0.89 and subjected to a uniform wall heat flux. In regards to the influence of rotation, both the centrifugal buoyancy and Coriolis forces are considered in the current study. The generalised model is used to mathematically simulate the momentum equations employing the Boussinesq approximation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 37 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…To this end, boundary conditions proposed by Ochoa-Tapia and Whitaker [32] for the fluid-solid interface are used with taking the thermal dispersion into account as detailed in Eqs. (11.a-e) mentioned previously by Alhusseny et al [19]. …”
Section: Mathematical Formulationmentioning
confidence: 60%
See 2 more Smart Citations
“…To this end, boundary conditions proposed by Ochoa-Tapia and Whitaker [32] for the fluid-solid interface are used with taking the thermal dispersion into account as detailed in Eqs. (11.a-e) mentioned previously by Alhusseny et al [19]. …”
Section: Mathematical Formulationmentioning
confidence: 60%
“…Also, their open-cell structure makes them less resistant to the fluids flowing through them, and hence, pressure drop across them is much less than it in the case of flow via packed beds or granular porous media. Therefore and due to their ability to meet the highly thermal demands with no excessive loss in pressure, open-cell metal foams have been utilised in heat exchangers [14], [15] besides internal cooling of both turbine blades [16] and the rotor windings of high-capacity electrical generators [17], [18], and [19]. Thus, it is not surprising to use them recently in double-pipe heat exchangers [20] and [21], where a substantial enhancement in the heat transfer performance has been acquired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, they have been proposed as an effective way to enhance the heat dissipated from heavy-duty electrical generators through filling their rotating cooling passages either fully or partially with open-cell metal foams [23][24][25]. The value of the this proposal was inspected by introducing an enhancement factor as the ratio of heat transported to the pumping power required, that is, Nu Re p in Àp e ðÞ =ρu 2 in , and comparing it with the corresponding values from a previous work regarding turbulent flow in a rotating clear channel [26], as shown in Figure 4 [25], where it was confirmed that the proposed enhancement is practically justified and efficient.…”
Section: Applicationsmentioning
confidence: 99%
“…Alhusseny et al [39] analyzed the distribution of the flow resistance and heat transfer coefficient in square channels partially filled with a metal foam for different filling rates, ε values, pore densities, and Re values (250~2000). Heat transfer was found to increase significantly as the filling rate and foam ε decreased or as Re increased.…”
Section: Introductionmentioning
confidence: 99%